2013
DOI: 10.1016/j.biortech.2013.02.096
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the retained sludge in a down-flow hanging sponge (DHS) reactor with emphasis on its low excess sludge production

Abstract: Experiments to characterize retained sludge in a down-flow hanging sponge (DHS) reactor fed with upflow anaerobic sludge blanket (UASB) treated sewage under moderate conditions were conducted. Plenty of oxygen was supplied through the DHS reactor without aeration and the effluent qualities after the reactor were comparable to activated sludge processes. The average excess sludge production rate was 0.09 g SS g(-1) COD removed. The DHS reactor maintained a high sludge concentration of 26.9 g VSS L(-1) sponge, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 31 publications
3
25
2
1
Order By: Relevance
“…The UASB þ DHS system showed sufficient removal of SS, BOD, and COD. These results were comparable to previous w a t e r r e s e a r c h 6 8 ( 2 0 1 5 ) 3 8 7 e3 9 3 reports using the same reactor system (Onodera et al, 2013;Takahashi et al, 2011). Water quality in the wastewater varied longitudinally in the DHS reactor as shown in Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The UASB þ DHS system showed sufficient removal of SS, BOD, and COD. These results were comparable to previous w a t e r r e s e a r c h 6 8 ( 2 0 1 5 ) 3 8 7 e3 9 3 reports using the same reactor system (Onodera et al, 2013;Takahashi et al, 2011). Water quality in the wastewater varied longitudinally in the DHS reactor as shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…The DHS reactor is a novel trickling filter using a sponge media as the sludge carrier in which bacteria and macrofauna are present (Kubota et al, 2014;Onodera et al, 2013). The DHS reactor in combination with the UASB has been verified as a reliable and efficient system for industrial and municipal wastewater treatment for over a decade (Machdar et al, 2000;Onodera et al, 2014;Tandukar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile analysis of the wastewater stream along the height of the G3-DHS bioreactor treating desluging septic tank wastewater showed that soluble COD (organic substance) and ammonia were removed mainly in the upper portion (Figure 2). This finding has also similar presented by other studies [7], [6], [9], [14]. It could be implied that the microenvironment almost certainly differs along the bioreactor height.…”
Section: Performances Of G3-dhs Bioreactorsupporting
confidence: 90%
“…In the virtue of longer sludge retention time, ample dissolved oxygen, endogenous respiration, microfaunal activity and good food/microorganism ratio, DHS even has the least excess sludge in comparison to other conventional treatment technologies (Tandukar et al, 2005(Tandukar et al, , 2007Onodera et al, 2013). The combined system of UASB-DHS has been considered as one of the most convincing technologies for municipal sewage treatment under variable conditions (Tandukar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%